Head and neck teratomas: two cases with rare localizations - Özdemir, Mehmet Akif; Patıroğlu, Tahir Ercan; Kurtoğlu, Selim; Telcioğlu, Mahmut (The Turkish Journal of Pediatrics, 1986)
Childhood teratomas with head-neck localization are rare and the tumors located in these regions have seldom a malignant character. Here two cases of teratoma, one benign and originating in the thyroid gland, the other malignant and developed in the oral cavity are presented and relevant literature is reviewed.